MENCEGAH STUNTING DALAM UPAYA MENGOPTIMALKAN PENGASUHAN SERIBU HARI PERTAMA KEHIDUPAN (HPK) DI MASA COVID-19 DESA PONDOKNONGKO KECAMATAN KABAT KABUPATEN BANYUWANGI - Ansari Ansari; Ina Rotul Ummah; Tina Kustrianingsih; Rika Raudotul Jannah (As-Sidanah, 2021)
Stunting is a problem that occurs in infants who are chronically malnourished and results in slow growth and development of babies, so it takes care by giving the first 1000 days of life to the baby. Methods of socialization and education of stunting prevention by optimizing the provision of nutrient intake to families or mothers who have babies by providing nutritional intervention specifically to infants who have been programmed to children aged 0-12 months, and children's mothers 13-24 months, because it is the most effective preventive measure on belita. In terms of stunting prevention, there has been a lot of innovation and progress from the central government, local governments, and all sectors of society.